Melanoma Mimicking Malignant Peripheral Nerve Sheath Tumor with Spread to the Cerebellopontine Angle: Utility of Next-Generation Sequencing in Diagnosis. (28th June 2018) - Fox Hanson, Katie; Birinyi, Paul; Walker, Ronald; Raptis, Constantine; Chernock, Rebecca; Coppens, Jeroen; Schwetye, Katherine E.
Abstract : Cutaneous spindle cell malignancy is associated with a broad differential diagnosis, particularly in the absence of a known primary melanocytic lesion. We present an unusually challenging patient who presented with clinical symptoms involving cranial nerves VII and VIII and a parotid-region mass, which was S100-positive while lacking in melanocytic pigment and markers. Over a year after resection of the parotid mass, both a cutaneous primary lentigo maligna melanoma and a metastatic CP angle melanoma were diagnosed in the same patient, prompting reconsideration of the diagnosis in the original parotid-region mass. Next-generation sequencing of a panel of cancer-associated genes demonstrated 19 identical, clinically significant mutations as well as a high tumor mutation burden in both the parotid-region and CP angle tumors, indicating a metastatic relationship between the two and a melanocytic identity of the parotid-region tumor.